From the New Diagnostic Criteria to COVID-19 Pandemic Passing Through the Placebo Effect. What Have We Learned in the Management of Pediatric Migrane Over the Past 5 Years? - Papetti, Laura; Tarantino, Samuela; Ursitti, Fabiana; Moavero, Romina; Proietti, Martina Checchi; Sforza, Giorgia; Monte, Gabriele; Ferilli, Michela Ada Noris; Balestri, Martina; Vigevano, Federico; Valeriani, Massimiliano (Frontiers in Neurology, 2022)
In 2018, the Food and Drug Administration (FDA) approval of anti-calcitonin gene-related peptide (CGRP) therapies for the treatment of migraine represented a milestone for the management of the disease in adults. On the contrary, the novelties in the field of pediatric migraine are inserted in a different scenario and still concern: (1) diagnostic criteria of the international classification of headache disorders-3 (ICHD-3) that show numerous limits of applicability in the developmental age; (2) the release of the results of the Childhood and Adolescent Migraine Prevention (CHAMP) study that raised doubts about the usefulness of traditional drugs for the treatment of pediatric migraine; (3) the Coronavirus disease 2019 (COVID-19) pandemic has put the spotlight on the importance of managing the psychological factors associated with the disease. In this mini review we discuss the most relevant news in pediatric migraine over the last 5 years.